Finding equation of tangent/normal when point and curve is given
Question 14 (i) Deleted for CBSE Board 2025 Exams
Question 22 Deleted for CBSE Board 2025 Exams
Question 24 Important Deleted for CBSE Board 2025 Exams
Question 7 Deleted for CBSE Board 2025 Exams
Question 5 Deleted for CBSE Board 2025 Exams You are here
Question 13 Important Deleted for CBSE Board 2025 Exams
Question 2 Deleted for CBSE Board 2025 Exams
Question 6 (MCQ) Deleted for CBSE Board 2025 Exams
Question 7 (MCQ) Important Deleted for CBSE Board 2025 Exams
Question 20 Deleted for CBSE Board 2025 Exams
Question 8 (MCQ) Important Deleted for CBSE Board 2025 Exams
Question 3 Important Deleted for CBSE Board 2025 Exams
Finding equation of tangent/normal when point and curve is given
Last updated at April 16, 2024 by Teachoo
Question 5 Find the equation of the tangent to the curve y = (𝑥 − 7)/((𝑥 − 2)(𝑥 − 3)) at the point where it cuts the x-axis.Slope of the tangent to the curve is 𝑑𝑦/𝑑𝑥 = ((𝑥 − 7)^′ [(𝑥 − 2) (𝑥 − 3)]− (𝑥 − 7) [(𝑥 − 3) (𝑥 − 2)]^′)/((𝑥 − 2)^2 (𝑥 − 3)^2 ) 𝑑𝑦/𝑑𝑥 = (1 × (𝑥 − 2) (𝑥 − 3) − (𝑥 − 7)[(𝑥 − 3)^′ (𝑥 − 2) + (𝑥 − 3) (𝑥 − 2)^′ ])/((𝑥 − 2)^2 (𝑥 − 3)^2 ) 𝑑𝑦/𝑑𝑥 = ((1) (𝑥 − 2) (𝑥 − 3) − (𝑥 − 7)[1 × (𝑥 − 2) + (𝑥 − 3) × 1])/((𝑥 − 2)^2 (𝑥 − 3)^2 ) 𝑑𝑦/𝑑𝑥 = ((𝑥 − 2) (𝑥 − 3) − (𝑥 − 7)(2𝑥 − 5))/((𝑥 − 2)^2 (𝑥 − 3)^2 ) 𝑑𝑦/𝑑𝑥 = ((𝑥 − 2) (𝑥 − 3) )/((𝑥 − 2)^2 (𝑥 − 3)^2 )−(𝑥 − 7)(2𝑥 − 5)/((𝑥 − 2)^2 (𝑥 − 3)^2 ) 𝑑𝑦/𝑑𝑥 = (1 )/((𝑥 − 2) (𝑥 − 3) )−((𝑥 − 7))/((𝑥 − 2) (𝑥 − 3) ) × ((2𝑥 − 5))/((𝑥 − 2) (𝑥 − 3) ) 𝑑𝑦/𝑑𝑥 = (1 )/((𝑥 − 2) (𝑥 − 3) )−𝑦 × ((2𝑥 − 5))/((𝑥 − 2) (𝑥 − 3) ) 𝒅𝒚/𝒅𝒙 = (𝟏 − 𝒚(𝟐𝒙 − 𝟓))/((𝒙 − 𝟐) (𝒙 − 𝟑) ) We need to find Equation of tangent at the point where the curve cuts the x axis, Thus, y = 0 We need to find value of x Putting y = 0 in equation of curve 0 = (𝑥 − 7)/(𝑥 − 2)(𝑥 − 3) ∴ x = 7 Thus, curve cuts the x-axis at point (7, 0) Finding Slope at point (7, 0) 𝑑𝑦/𝑑𝑥 = (1 − 𝑦(2𝑥 − 5))/((𝑥 − 2) (𝑥 − 3) ) Putting x = 7, y = 0 = (1 − 0[2(7)−5])/((7 − 2) (7 − 3) ) = 1/(5 × 4) = 𝟏/𝟐𝟎 Now, Equation of the tangent at point (7, 0) with slope 1/20 is 𝑦 −𝑦_1= 𝑚 (𝑥 − 𝑥1) 𝑦−0= 1/20 (𝑥−7) 20𝑦=𝑥−7 𝟐𝟎𝒚−𝒙+𝟕=𝟎